Proceedings of the Twenty-Seventh Annual ACM-SIAM Symposium on Discrete Algorithms 2015
DOI: 10.1137/1.9781611974331.ch2
|View full text |Cite
|
Sign up to set email alerts
|

New directions in nearest neighbor searching with applications to lattice sieving

Abstract: To solve the approximate nearest neighbor search problem (NNS) on the sphere, we propose a method using locality-sensitive filters (LSF), with the property that nearby vectors have a higher probability of surviving the same filter than vectors which are far apart. We instantiate the filters using spherical caps of height 1 − α, where a vector survives a filter if it is contained in the corresponding spherical cap, and where ideally each filter has an independent, uniformly random direction.For small α, these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
236
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 208 publications
(240 citation statements)
references
References 29 publications
3
236
0
1
Order By: Relevance
“…The best squeezing method we found uses vpmulhrsw, which performs 16 separate copies of the following operation: multiply two integers between −2 15 and 2 15 , divide by 2 15 , and round to an integer. We take the second integer as 7; then the output is round(7x/2 15 ) where x is the first integer.…”
Section: Choosing Haswell Multiplication Instructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best squeezing method we found uses vpmulhrsw, which performs 16 separate copies of the following operation: multiply two integers between −2 15 and 2 15 , divide by 2 15 , and round to an integer. We take the second integer as 7; then the output is round(7x/2 15 ) where x is the first integer.…”
Section: Choosing Haswell Multiplication Instructionsmentioning
confidence: 99%
“…Now we rewrite f m as p−1 i=0 f i (x i m). Since this sum adds at most 2t terms of each degree, it just remains to be shown that the coefficients of [15,79]) has pushed the heuristic complexity down to 2 0.292...β+o(β) .…”
Section: Proof Of Theorem 21mentioning
confidence: 99%
“…The remaining part of this subsection is dedicated to proving (11) and (12). We first prove that nearby vectors often collide in at least one of the hash tables, given that k is a suitable function of t. We then show how p * 2 scales as a function of k and t and how to choose k and t to minimize the asymptotic time complexity.…”
Section: A Proof Of Theoremmentioning
confidence: 99%
“…Although this work focuses on applying angular LSH to sieving, more generally this work could be considered the first to succeed in applying LSH to lattice algorithms. Various recent followup works have already further investigated the use of different LSH methods [7,8] and other nearest neighbor search methods [9,11,38] in the context of lattice sieving [11][12][13]30,37], and an open problem is whether other lattice algorithms (e.g. provable sieving algorithms, the Voronoi cell algorithm [39]) can benefit from related techniques as well.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first data structure that achieves sublinear query time and near-linear space for every approximation factor c > 1, improving upon [Kap15]. The data structure is a culmination of a long line of work on the problem for all space regimes; it builds on Spherical Locality-Sensitive Filtering [BDGL16] and datadependent hashing [AINR14,AR15]. Our matching lower bounds are of two types: conditional and unconditional.…”
Section: Introductionmentioning
confidence: 99%